Demand for Pharmaceuticals: Impacts on Production and Employment in Nearly Every Sector of the Economy - Jörg-Peter Weiss; Stephan Raab; Joachim Schintke (Weekly Report, 2005)
The pharmaceutical industry employs around 106 000 people and produces a good 9 billion euros or 2.5% of value added in the manufacturing sector in Germany. But it contributes a bigger part to value added and employment in the economy as a whole than these figures show. Its particular role results from the fact that almost its entire output (96%) goes direct to end user (final demand), while demand for its products is subject to the special regulations in the health system. With its purchases of intermediate products and capital goods the pharmaceutical industry gives rise to production and employment effects in nearly every area of production. That applies particularly to high quality services, like business-related services, research and development, leasing, services in the real estate and housing sector and data processing and data bank services. State regulations in the health system thus also have an effect in other sectors of the economy. This article presents analyses by DIW Berlin of the linkages between the pharmaceutical industry and the rest of the economy. It shows that deliveries by the pharmaceutical sector to final demand in private households and public authorities (the social insurance institutions, especially the compulsory health insurance) and abroad have considerable indirect production effects in other sectors of the economy, amounting to about 60% of the direct deliveries by the pharmaceutical industry to final demand. So for every person employed in the pharmaceutical industry one other person is employed in the rest of the economy.
Keywords: 330